Zastrzeżenia do statutów organizacji międzynarodowych: [Reservations on the statutes of international organisations] (Studia Prawnicze / The Legal Studies, 2023)
Celem opracowania jest przedstawienie aktualnego stanu faktycznego i prawnego w dziedzinie zastrzeżeń do statutów organizacji międzynarodowych oraz wskazanie rozwiązań które mogłyby wypełnić luki występujące w systemie stworzonym przez konwencje wiedeńska tworząc wraz z nim logiczna całość. Autorka artykułu porusza kwestie dopuszczalności zgłaszania zastrzeżeń do statutów. Ponadto przedstawia zagadnienia dot. Podmiotów, które kompetentne do przyjmowania zastrzeżeń zgłaszanych do statutów i wyrażania sprzeciwów wobec nich. Kolejnym problemem są skutki prawne uchwal ww. organów w sprawie zastrzeżeń zgłoszonych do statutów. Autorka opisuje skutki sprzeciwów indywidualnych dot. zastrzeżeń złożonych do statutów. Porównuje także zwykle traktaty wielostronne ze statutami organizacji międzynarodowych pod względem częstotliwości i liczby składanych zastrzeżeń. The purpose of this study is to present the current factual and legal situation in the field of reservations to the statutes of international organisations and to identify solutions that could fill the gaps in the system created by the Vienna Convention, forming a logical whole with it. The author of the article addresses the admissibility of objections to statutes. In addition, she presents issues concerning entities competent to receive objections raised to the statutes and express objections to them. Another problem is the legal effect of the resolutions of the aforementioned bodies on the objections raised to the statutes. The author describes the effects of individual objections to objections made to statutes. Typical multilateral treaties are also compared with statutes of international organisations in terms of the frequency and number of reservations made.